Beyond the horizon adventures in faraway lands - Booz, Patrick R.; Aaronson, Jeffrey (The National Geographic Society, 1992)
Travel to some of the world's least known places including Timbuktu in Africa, Muli on the China-Tibet border, and to Iceland.